Atomic scale configuration of planar defects in the Nb-rich C14 Laves phase NbFe2. (15th January 2020) - Šlapáková, M.; Zendegani, A.; Liebscher, C.H.; Hickel, T.; Neugebauer, J.; Hammerschmidt, T.; Ormeci, A.; Grin, J.; Dehm, G.; Kumar, K.S.; Stein, F.
Abstract: Laves phases belong to the group of tetrahedrally close-packed intermetallic phases, and their crystal structure can be described by discrete layer arrangements. They often possess extended homogeneity ranges and the general notion is that deviations from stoichiometry are accommodated by anti-site atoms or vacancies. The present work shows that excess Nb atoms in a Nb-rich NbFe2 C 14 Laves phase can also be incorporated in various types of planar defects. Aberration-corrected scanning transmission electron microscopy and density functional theory calculations are employed to characterize the atomic configuration of these defects and to establish stability criteria for them. The planar defects can be categorized as extended or confined ones. The extended defects lie parallel to the basal plane of the surrounding C 14 Laves phase and are fully coherent. They contain the characteristic Zr4 Al3 -type (O) units found in the neighboring Nb6 Fe7 µ phase. An analysis of the chemical bonding reveals that the local reduction of the charge transfer is a possible reason for the preference of this atomic arrangement. However, the overall layer stacking deviates from that of the perfect µ phase. The ab initio calculations establish why these exceptionally layered defects can be more stable configurations than coherent nano-precipitates of the perfect µ phase. The confined defects are observed with pyramidal and basal habit planes. The pyramidal defect is only 1 nm thick and resembles the perfect µ phase. In contrast, the confined basal defect can be regarded as only one single O unit and it appears as if the stacking sequence is disrupted. This configuration is confirmed by ab initio calculations to be metastable. Graphical abstract: Image, graphical abstract